Fly ash hollow glass microballon brightens production line - LI ZHENGNAN; AN JIANXIA (2017)
The utility model discloses a bleaching production line of fly ash glass bead, to current production technology can not be fine recovery coal ash, the cyclic utilization that waste water in the production process can not be fine, bleach defects such as not thorough, but provides one kind and can realize by -product recycle, the low cost can realize automatic serialization and produce the production line. 本实用新型公开了种粉煤灰玻璃微珠漂白的生产线，针对现有生产工艺不能很好的回收煤灰、生产过程中的废水不能很好的循环利用，漂白不彻底等缺陷，提供种可实现副产品可回收利用，低成本，可实现自动化连续化生产生产线。